1984
DOI: 10.1007/bf01296226
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic arterial embolization for malignant hypercalcemia in hepatocellular carcinoma

Abstract: A patient who presented with hypercalcemia was found to have an hepatocellular carcinoma. Medical treatment failed to normalize blood calcium levels. Liver resection was not feasible due to major extrahepatic involvement. Selective arterial embolization of the tumor was performed, resulting in correction of the hypercalcemia. This observation suggests that some life-threatening complications of unresectable hepatocellular carcinoma can be treated by arterial embolization of the tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Treatment of HCC, either via surgical resection or TACE, has been shown to abrogate PNS [16]. Paraneoplastic activity is related to overall tumor burden and biological activity of the neoplastic hepatocytes, which are significantly reduced with effective treatment of the disease and may reappear in tandem with recurrence of HCC [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Treatment of HCC, either via surgical resection or TACE, has been shown to abrogate PNS [16]. Paraneoplastic activity is related to overall tumor burden and biological activity of the neoplastic hepatocytes, which are significantly reduced with effective treatment of the disease and may reappear in tandem with recurrence of HCC [17]. …”
Section: Discussionmentioning
confidence: 99%
“…The association between hypercalcemia and hepatic malignancy is rare, with a prevalence ranging from 1.5% to 40% in different reports (3,12). It was suggested that the inclusion or exclusion of patients with documented metastasis might have accounted for this big variation.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercalcemia has been described mainly with hepatocellular carcinoma and cholangiocarcinoma (3). A distinct histological subtype called 'sclerosing hepatic carcinoma' has been strongly linked to hypercalcemia in the absence of bony metastasis (10,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported incidence of primary hepatic tumors with hypercalcemia ranges from 1.5% to 40% (1,2). The patients with metastasis may or may not have been included in these studies, which would account for the wide variation.…”
Section: Introductionmentioning
confidence: 99%